Social Activity of Man and Morality - Kapačiauskienė, Danutė (Problemos, 1985)
The problem of socio-historical conditionality of possibilities of an individual to be a moral personality is raised. The term ‘human activity’ is proposed as a point of departure in the analysis of the conditionality. The qualities of human activity, namely, its material and active character representing the objective basis of natural morality are cleared up. In the process of alienation these qualities setting apart a disturbance of the natural morality occurs making the second-grade foundations of morality significant. Those second-grade foundations are not reproduced in everyday activity of a personality as value attitudes but are brought from outside through moral teachings.